2001
DOI: 10.1099/0022-1317-50-1-83
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterisation of an anticryptococcal protein in human cerebrospinal fluid

Abstract: An earlier study reported that human cerebrospinal¯uid (CSF) has fungistatic activity for Cryptococcus neoformans. The present study reports that molecular sieve fractionation of concentrated CSF yielded three protein peaks, one of which (p2) had anticryptococcal activity. On a DEAE-Sephacel anion-exchange column the active molecular sieve peak (p2) gave two peaks that contained anticryptococcal activity. The ®rst (DEAE-1) eluted with 0.1 M NaCl and the second (DEAE-2) eluted with 0.2 M NaCl in buffer. Fungist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…It is well known that serum albumin is the most abundant protein in the circulatory system and it possesses many important physiological functions that contribute to colloid osmotic blood pressure and aid in the transport, distribution and metabolism of many endogenous and exogenous substances. In addition, it was reported that albumin might play an important role in innate immunity ( Fassi et al 1993 , Brummer et al 1999 , Ahluwalia et al 2001 ). Giles and Czuprynski (2003) showed that the albumin from several mammalian species had obvious inhibitory activity against Blastomyces dermatitidis , while analbuminaemic rat serum failed to inhibit B. dermatitidis growth in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that serum albumin is the most abundant protein in the circulatory system and it possesses many important physiological functions that contribute to colloid osmotic blood pressure and aid in the transport, distribution and metabolism of many endogenous and exogenous substances. In addition, it was reported that albumin might play an important role in innate immunity ( Fassi et al 1993 , Brummer et al 1999 , Ahluwalia et al 2001 ). Giles and Czuprynski (2003) showed that the albumin from several mammalian species had obvious inhibitory activity against Blastomyces dermatitidis , while analbuminaemic rat serum failed to inhibit B. dermatitidis growth in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…The increased abundance of a tag corresponding to the phosphate transporter in vivo correlates well with our identification of an increased abundance of tags for genes encoding the electron transport chain. Iron in the CSF is bound to brain-derived transferrin, and the availability of iron for C. neoformans is thought to be limited during infection (1). This finding correlated with the significant increase in the abundance of a tag corresponding to an iron permease gene observed under in vivo conditions relative to in vitro conditions.…”
Section: Vol 2 2003 Cryptococcus Neoformans Transcription In Vivo 1343mentioning
confidence: 91%
“…Transferrin and lactoferrin are known to have an inhibitory effect on the growth of the pathogenic fungi A. fumigatus , C. albicans and C. neoformans (Sridhar et al, 2000 ; Ahluwalia et al, 2001 ; Lahoz et al, 2008 ; Almeida et al, 2009 ; Kornitzer, 2009 ; Okazaki et al, 2009 ). The mechanism of inhibition is probably due to iron sequestration by partially iron-loaded protein because additional studies have shown that these fungi can acquire iron from fully iron-loaded transferrin under specific conditions.…”
Section: Iron Acquisition From Transferrin Lactoferrin and Ferritinmentioning
confidence: 99%